Soil CO2 efflux and extractable organic carbon fractions under simulated precipitation events in a Mediterranean Dehesa - Casals, Pere; Gimeno, Cristina; Carrara, Arnaud; Lopez-Sangil, Luis; Sanz, MJosé (Soil Biology and Biochemistry, 2009)
The magnitude of CO2 efﬂux pulses after rewetting a dry soil is highly variable and the factors regulating these pulses are poorly understood. In this ﬁeld experiment, we aimed to study the C dynamics after simulated summer rainstorms in a Mediterranean open holm oak woodland (dehesa). We hypothesized that because the herbaceous cover is mostly dead during the summer in this ecosystem, the short-term CO2 efﬂux (SR) after rewetting could mainly be explained by different measurable soil C fractions: i) K2SO4-extracted soil C (EOC); ii) microbial biomass C (MBC); or iii) chloroform-fumigated extracted C (CFE). On both grazed and abandoned dehesa sites, we simulated three summer rain events at two-week intervals and we measured SR discontinuously in three plots under tree canopy and in another three plots in open grassland. In each plot, C fractions and water content were estimated before (2 h) and after (36 h) each irrigation event. Following rewettings, SR increased up to ten times compared with nonirrigated plots. The CFE actually increased after rewetting in the ﬁrst two irrigations but not in the third event, suggesting that the capacity of the soil to release labile organic C from soil aggregates or litter was reduced after each irrigation event. Overall, the C released as CO2 in the ﬁrst 24 h was related to the CFE existing before rewetting, which may help to explain the spatial variability in SR. However, the explained variability decreased after each irrigation, suggesting a change to a less labile composition of the CFE fraction as a consequence of multiple drying-rewetting cycles
Keywords: Chloroform-fumigation K2SO4-extraction; drying-rewetting cycles; holm oak savanna woodland; Soil C fractions; Soil respiration

Soil CO2 efflux and extractable organic carbon fractions under simulated precipitation events in a Mediterranean Dehesa (Soil Biology and Biochemistry, 2009)
The magnitude of CO2 efﬂux pulses after rewetting a dry soil is highly variable and the factors regulating these pulses are poorly understood. In this ﬁeld experiment, we aimed to study the C dynamics after simulated summer rainstorms in a Mediterranean open holm oak woodland (dehesa). We hypothesized that because the herbaceous cover is mostly dead during the summer in this ecosystem, the short-term CO2 efﬂux (SR) after rewetting could mainly be explained by different measurable soil C fractions: i) K2SO4-extracted soil C (EOC); ii) microbial biomass C (MBC); or iii) chloroform-fumigated extracted C (CFE). On both grazed and abandoned dehesa sites, we simulated three summer rain events at two-week intervals and we measured SR discontinuously in three plots under tree canopy and in another three plots in open grassland. In each plot, C fractions and water content were estimated before (2 h) and after (36 h) each irrigation event. Following rewettings, SR increased up to ten times compared with nonirrigated plots. The CFE actually increased after rewetting in the ﬁrst two irrigations but not in the third event, suggesting that the capacity of the soil to release labile organic C from soil aggregates or litter was reduced after each irrigation event. Overall, the C released as CO2 in the ﬁrst 24 h was related to the CFE existing before rewetting, which may help to explain the spatial variability in SR. However, the explained variability decreased after each irrigation, suggesting a change to a less labile composition of the CFE fraction as a consequence of multiple drying-rewetting cycles